PELAKSANAAN PENYIDIKAN OLEH KEJAKSAAN TINGGI RIAU DALAM PERKARA TINDAK PIDANA KORUPSI TERHADAP KERUGIAN KEUANGAN NEGARA - Novianti, Tri; ', Erdianto; ', Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Indonesia is one of country with a number of corruption cases which is quite a lot. Literally corruption is something rotten , evil and destructive. Cases of corruption are generally difficult to describe because the perpetrators use sophisticated equipment and are usually carried out more than one person in a state of covert and organized. Such criminal acts in general , corruption is also through the completion of the investigation in the case. In the Criminal Code provisions that the prosecutor could not explain investigator. However , the corruption prosecutors are empowered to become investigators and investigate a case of alleged corruption .In the cases crime of corruption are the provision of Article 25 of Law No. 31 of 1999 on Corruption Eradication in which the core of the article is